Selection of Materials Used in Viscous Clutch With ER Fluid Working in Special Conditions - Olszak, Artur; Osowski, Karol; Motyl, Przemysław; Mędrek, Grzegorz; Zwolak, Jan; Kęsy, Andrzej; Kęsy, Zbigniew; Choi, Seung-Bok (Frontiers in Materials, 2019)
This article presents considerations regarding materials used to fabricate a hydraulic clutch with an ER fluid operating in non-standard working conditions. The hydraulic clutch was a subassembly of the device used for exerting a controlled force on the stationary object. This clutch was driven by an electric motor. The force was controlled by changing the shear stresses in the ER fluid. Shear stresses were changed in two ways: by changing the angular velocity of the electric motor and by changing the high voltage applied to the electrodes located on the driving part and the driven part of the clutch. The increase in these stresses caused an increase in the torque transmitted and an increase in the pressure force. In order to construct the clutch, mathematical models based on the Bingham model were developed, which took into account the influence of temperature and humidity on the shear stress in the ER fluid, allowing calculation of the clutch performance. In addition, numerical calculations of the temperature distribution inside the clutch were carried out using the ANSYS program because of the intense heat generation during the clutch operation. The developed mathematical models were used to optimize the clutch. The aim of the optimization was to obtain a high transmitted torque with small dimensions of the clutch, taking into account the thermal capacity of the clutch. Based on the optimization results, a prototype of a hydraulic clutch with an ER fluid was designed and made, assuming that for metal materials their anti-corrosion properties are the most important, since the presence of conductive metal oxides causes electrical breakdowns. The plastics used in the clutch prototype were mainly evaluated for insulating properties and high temperature resistance. When choosing the ER fluid, its sensitivity to temperature and humidity as well as durability were taken into account. The clutch prototype has been tested on a specially built test rig. The test results confirmed the proper selection of both construction materials and ER fluids. Based on the results of these tests, guidelines for the construction of clutches with ER fluids were formulated.